2018
DOI: 10.1177/1534735418781725
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clown Intervention on Self-Report and Biomarker Measures of Stress and Fatigue in Pediatric Osteosarcoma Inpatients: A Pilot Study

Abstract: Background: Pediatric cancer patients experience different psychological processes during hospitalization that may regulate the immune response and affect recovery and response to cancer treatment. In this study, we aimed to examine the feasibility of longitudinal testing of psychophysiological parameters of stress and fatigue in pediatric osteosarcoma patients hospitalized for chemotherapy submitted to clown intervention; and to investigate whether changes in the levels of biomarkers are associated with psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 74 publications
1
30
0
3
Order By: Relevance
“…49 All the studies were single centre trials, and most included male and female patients (n=23). 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 63 64 65 66 67 68 69 Only one study exclusively included male patients 62 because the study population included children undergoing outpatient penile surgery. Fourteen studies exclusively involved children in hospital (age 2-12), 46 47 48 49 50 52 57 59 60 61 62 63 64 67 and the 10 remaining studies included both children and adolescents in hospital (age 13-18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 All the studies were single centre trials, and most included male and female patients (n=23). 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 63 64 65 66 67 68 69 Only one study exclusively included male patients 62 because the study population included children undergoing outpatient penile surgery. Fourteen studies exclusively involved children in hospital (age 2-12), 46 47 48 49 50 52 57 59 60 61 62 63 64 67 and the 10 remaining studies included both children and adolescents in hospital (age 13-18).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies exclusively involved children in hospital (age 2-12), 46 47 48 49 50 52 57 59 60 61 62 63 64 67 and the 10 remaining studies included both children and adolescents in hospital (age 13-18). 51 53 54 55 56 58 65 66 68 69 The mean sample size among studies was 67.16 (standard deviation 57.22, range 6-306). 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study has not assessed the cost-effectiveness of the HC practice, their intervention may reduce the costs often associated with cancer treatment, by lowering the patient's negative emotions and physical symptoms and increasing their well-being while they undertake the chemotherapy treatment prescribed for their condition. Nevertheless, because the research with HCs is still scarce (Lopes-Júnior et al 2018;Petrangeli et al 2012;Gorfinkle et al 1998), the benefits associated with their work merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the favorable results of HC's intervention with pediatric populations, less research has been conducted with other procedures such as cancer treatment. To our knowledge, there are only three studies in this area: two reported in conference proceedings (Petrangeli et al 2012;Gorfinkle et al 1998) and one pilot study (Lopes-Júnior et al 2018). Petrangeli et al (2012) indicated that HCs reduced fatigue in patients aged 7-18 years undergoing chemotherapy, whereas Gorfinkle et al (1998) found no effects from HC presence on distress among 3-18 years old patients.…”
Section: Introductionmentioning
confidence: 99%